Bob's toolbox mix-up - Thorpe, Kiki; Mendenhall, Cheryl (New York : Simon Spotlight, 2002)
"Bob can't finish up Wendy's house until he finds his missing hammer. Help Bob and the team search for it in this silly, mixed-up lift-the-flap story."--Cover.
"With 18 flaps!"--Cover.
"Based upon the television series Bob the builder created by HIT Entertainment PLC and Keith Chapman, with thanks to HOT Animation."--Cover.
On board pages.
Keywords: Children's stories; Toy and movable books -- Specimens